Why Do Nascent ICT Businesses Die Young? - Mayoka, Kituyi G.; Balunywa, Waswa (Journal of Research in International Business and Management, 2012)
This study sought to investigate why most nascent ICT businesses failed during their early stages in Uganda along the constructs of the family business sustainability model. A quantitative survey research design was adopted and used, in which a self-administered questionnaire was the main data collection tool. Primary data were analyzed using descriptive statistics. The key factors influencing ICT business start-up were identified as unemployment, the need to get side income, create jobs for family members and get rich. Findings also indicate that most nascent ICT businesses failed because proprietors employed relatives, were not available and committed to their businesses. In addition, excessive competition from foreign products, lack of business management and entrepreneurship skills, financial indiscipline, mistrust, poor savings culture, conflict of interest between managers and family members and failure to pay bank loans, rent and taxes were also responsible for ICT business failures. The study indentified the most salient policy innervations for sustainable ICT businesses in Uganda as reduced interest rates, training in ICT and entrepreneurship skills, availability of business soft loans, government subsidies, establishment of business incubation centers and controlled inflow of foreign ICT products.
Keywords: ICT Businesses; Family business; Small businesses; Sustainability; Uganda; Business Failures; Entrepreneurial tendencies